A computational subtractive genome analysis for the characterization of novel drug targets in Klebsiella pneumonia strain PittNDM01. (September 2020) - Rafiq, Humaira; Ullah, Kalim; Ahmad, Bashir; Rehman, Ashfaq Ur; Shah, Mian Khaqan; Khan, Ajmal; Uddin, Reaz; Azam, Syed Sikander; Wadood, Abdul
Abstract: The emergence of carbapenem-resistant Klebsiella Pneumoniae had been reported previously, which needs rapid attention. Currently, Pittsburgh University Hospital reported a new strain of carbapenem-resistant Klebsiella pneumoniae that was co-producing OXA-232 and NDM-1 named as PittNDM01. This strain is resistant to almost all beta-lactam antibiotics such as Carbapenem as well as to fluoroquinolones and aminoglycosides. Globally, failure to the wide-spread pathogenic strains had been observed due to the increased and antibiotic resistance, which leads to less antimicrobial drug efficacy. Since last decades, computational genomic approaches have been introduced to fight against resistant pathogens, which is an advanced approach for novel drug targets investigation. The current study emphasizes the utilization of the available genomic and proteomic data of Klebsiella pneumoniae PittNDM01 for the identification of novel drug targets for future drug developments. Comparative genomic analysis and molecular biological tools were applied, results in observing 582 non-human homologous-essential proteins of Klebsiella pneumoniae . Among the total 582 proteins, 66 were closely related to the pathogen-specific pathway. Out of all 66-targeted proteins, ten non-homologous essential proteins were found to have druggability potential. The subcellular localization of these proteins revealed; 6 proteins in the cytoplasm, 2 in the inner membrane, and one each in periplasmic space and outer membrane. All the above 10 proteins were compared to the proteins sequences of gut flora to eliminate the homologous proteins. In total, 6-novel non-human and non-gut flora essential drug targets of Klebsiella pneumoniae PittNDM01 strain were identified. Further, the 3D structures of the identified drug target proteins were developed, and protein-protein interaction network analysis was performed to know the functional annotation of the desire proteins. Therefore, these non-homologous essential targets ensure the survival of the pathogen and hence can be targeted for drug discovery. Highlights: Subtractive genome analysis. Novel drug targets in Klebsiella pneumonia. Prediction of 3D structures of target proteins. Prediction of protein-protein interaction.